Nutritional status of primary school children - Manandhar, N.; Krishna, G.; Patowary, S. (Journal of Institute of Medicine Nepal, 2008)
Background: Malnutrition is one of the major public health problems in Nepal. The nutritional and morbidity status are indicators of the level of the quality of life of school children. Good health and adequate nutrition promote both physical growth and learning.Methods: This study is a cross sectional study carried out during the period of August-September, 2006. The study population was the school children of Nursery to class five. One of the Government school is selected at randomly in Bharatpur.Results: 11.38% of school children were below 80% weight for age i.e. under nutrition. According to Waterlow classification, among total school children, 89.85% were normal, 7.69% of school children were stunted and 3.38% of children were found to be wasted. Skin diseases (21.45%) were common in school children. Dental carries were found in 16.0% of school children followed by history of Worm infestation in 10.77%.Discussion: The results of our study were quite encouraging when compared with other studies conducted in different parts of Nepal. This may be due to good water supply, better environmental conditions, good facilities for excreta disposal & health care facilities in the study area.Conclusion: The nutritional status of primary school children in this study were found to be satisfactory when compared with other studies conducted in different parts of Nepal. The health education should be given on control and prevention of different diseases.